The Mediating role of competitiveness in the relationship between managerial creativity and tourism enterprise performance: Evidence from Yemen - Al-Khazzan, Abdulhafeedh Yahya M.; Alrahomi, Ahmed Ahmed (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the mediating role of competitiveness in the relationship between managerial creativity and the tourism enterprise performance in unstable and resource-limited contexts such as Yemen. Although creativity plays a key role in enhancing organizational performance, the role of competitiveness as a mediator in this relationship remains underexplored, particularly in contexts facing similar challenges. Employing a quantitative, cross-sectional survey design, data were collected from 472 general managers and executive directors representing 256 tourism companies affiliated with the Yemen Union for Tourism (YUT). The questionnaire, grounded in established prior research, captured dimensions of managerial creativity, competitiveness, and enterprise performance. Data analysis involved descriptive statistics, correlation tests, and mediation analysis using Hayes’ PROCESS macro, with reliability confirmed through Cronbach’s alpha and minimal common method bias verified by Harman’s single-factor test. The results reveal that managerial creativity positively influences both competitiveness and performance, while competitiveness serves as a key mediator that strengthens the relationship between managerial creativity and tourism enterprise performance by improving resource utilization, integrating technology, and enhancing service quality. Managerial creativity contributes to higher organizational outcomes when combined with strong competitiveness. The study underscores that enhancing competitiveness enables tourism enterprises to better leverage creative initiatives for sustainable performance in challenging environments. Moreover, combining innovative management practices with strategic investments in organizational efficiency, infrastructure, and human capital can foster sustainable growth and strengthen the resilience of Yemeni tourism enterprises. Tourism policymakers and managers should foster a culture of creative management and strategically invest in infrastructure and human capital. Such actions can enhance competitiveness, drive sustainable growth, and enhance the resilience of tourism enterprises in Yemen and similar developing contexts.